A contribuição de Henri Lefebvre para reflexão do espaço urbano da Amazônia - Charles Benedito Gemaque Souza (Confins)
The space considered as historically produced by man in organizing both political and economical his society; this is the affirmation that distinguishes Henri Lefebvre masterpieces. It deals with a concrete attempt in returning to the Marx dialectic, but without the dogmatism the characteristic oppressions concerning other materialist interpretations. However, the present time of the actor reflection inherent to the Amazon urban space and in assignment with its socio-spatial presented in Belém day-to-day allows the exercise of the validity acknowledgment of such thought along with apprehension of the Amazon city complexity.